The effect of canopy temperature depression in Barley crop on different environmental sowing conditions in Trans-Gangetic plains of India - Navreet, B; Surender, S; Chander, D S; Pankaj, D (Plant Science Today, 2025)
A study on barley crops was carried out at the research farm of the Department of Agricultural Meteorology during the Rabi season of 2019-20 and 2020-21. The trial objective was to understand the effect of various meteorological, plant and soil parameters on the Canopy Temperature Depression (CTD) of barley crops under varying growing environmental conditions. Four dates of sowings were selected for both rabi seasons of 2019-20 and 2020-21, i.e., D1- 15th November 2019, D2- 30th November 2019, D3- 15th December 2019 and D4- 30th December 2019 and D1- 28th November 2020, D2- 14thDecember 2020, D3- 28thDecember 2020 and D4- 8 th January 2021. The meteorological parameters were taken from the agrometeorological observatory at the research farm of CCS HAU, Hisar. Plant and soil parameters were recorded and calculated during the field trials conducted on barley crops in both seasons (2019-20 and 2020-21). The CTD of the barley crop was observed using a hand-held infrared thermometer at different phenological stages. It was observed that the CTD of D1 and D2 sown crops was majorly influenced by meteorological and soil parameters, respectively. The plant parameters majorly influenced the CTD of D3and D4 sown crops.